2021
DOI: 10.1101/2021.11.17.468836
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cooperative protein allosteric transition mediated by a fluctuating transmission network

Abstract: Allosteric communication between distant protein sites represents a key mechanism of biomolecular regulation and signal transduction. Compared to other processes such as protein folding, however, the dynamical evolution of allosteric transitions is still not well understood. As example of allosteric coupling between distant protein regions, we consider the global open-closed motion of the two domains of T4 lysozyme, which is triggered by local motions in the hinge region. Combining extensive molecular dynamics… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…On the other hand, we expect that the main finding, i.e., that allosteric communication is mediated through a concerted conformational transition that involves numerous simultaneous contact changes, prevails also in the absence of direct contacts and therefore represents a general result. For example, Post et al 44 found a quite similar scenario for the allosteric coupling in T4 lysozyme.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…On the other hand, we expect that the main finding, i.e., that allosteric communication is mediated through a concerted conformational transition that involves numerous simultaneous contact changes, prevails also in the absence of direct contacts and therefore represents a general result. For example, Post et al 44 found a quite similar scenario for the allosteric coupling in T4 lysozyme.…”
Section: Discussionmentioning
confidence: 92%
“…To identify internal coordinates that change significantly during the conformational transition, we follow recent work 43,44 and focus on interresidue contact distances. This is for two reasons.…”
Section: Correlation Analysis Of Interresidue Contactsmentioning
confidence: 99%
See 2 more Smart Citations
“…3c, which shows that these distances span the space connecting the mouth and hinge regions, and therefore reflect the allosteric coupling between these two distant regions. 69 Largely uncorrelated to cluster 1, clusters 2 and 3 account for other correlated motions of T4L. As shown in Fig.…”
Section: Functional Dynamics Of T4 Lysozymementioning
confidence: 88%